2023
DOI: 10.1093/plcell/koad139
|View full text |Cite
|
Sign up to set email alerts
|

Efficient protein tagging and cis-regulatory element engineering via precise and directional oligonucleotide-based targeted insertion in plants

Abstract: Efficient and precise targeted insertion holds great promise but remains challenging in plant genome editing. An efficient non-homologous end-joining-mediated targeted insertion method was recently developed by combining CRISPR/SpCas9 gene editing with phosphorothioate modified double-stranded oligodeoxynucleotides (dsODNs). Yet this approach often leads to imprecise insertions with no control over the insertion direction. Here, we compared the influence of chemical protection of dsODNs on efficiency of target… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Moreover, the multiplex PE system can serve as a valuable asset for functional genomics by enabling researchers to change the native gene sequence instead of relying on complementation assays with a transgenic approach. Multiple protein tagging with PE can help us understand complex gene-regulatory networks by tracking protein expression in native conditions ( Hua et al., 2022 ; Kumar et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the multiplex PE system can serve as a valuable asset for functional genomics by enabling researchers to change the native gene sequence instead of relying on complementation assays with a transgenic approach. Multiple protein tagging with PE can help us understand complex gene-regulatory networks by tracking protein expression in native conditions ( Hua et al., 2022 ; Kumar et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent efforts to extend CRISPR-Cas9 genome editing into plants have confirmed the prevalence of 1-bp insertions in various plant species 9,[16][17][18] . While these findings suggested a potential extension of predictability observed in animals to plants, recent studies have also indicated that 1-bp insertion profiles may not be consistently predictable as proposed by the templated insertion model 9,16,17 . The existence of distinctive 1-bp insertion profiles and the underlying mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Heritable GT can be enhanced by specifically expressing CAS9 in egg cells or embryos (Wang et al, 2015; Wolter et al, 2018). Note that while we focus here on procedures involving double strand breaks and homology‐directed repair, recent work has also reported GT methods that utilise NHEJ to insert new sequence (e.g., Cermak, 2021; Kumar et al, 2023).…”
mentioning
confidence: 99%